Conflitos ambientais e a atuação do Núcleo de Resolução de Conflitos Ambientais NUCAM do Ministério Público do Estado de Minas Gerais - Paulo Henrique Campos Leite (2018)
This research aims to study the treatment of environmental conflicts by the Public Ministry as an institution focused on the defense of collective interests. In this sense, the problem in focus is the role of the Public Prosecutor in cases involving environmental conflicts and how the institution has incorporated self-assessment methods, such as mediation, as an instrument for the resolution of these conflicts. The research also intends to analyze the Public Prosecution Service of the State of Minas Gerais' strategies and performance profiles in environmental conflict resolution. For this, we reviewed the original sources at the Public Prosecutor's Office, mostly the sources at the Environmental Conflict Resolution Center-NUCAM, such as archives, civil inquiries and administrative procedures. The examination performed on the NUCAM archive data shows that the self-assessment methods applied by the Public Prosecutor's Office contribute to the resolution of some environmental conflicts. However, the data also indicates that this method alone is not capable of solving each and every case. Thus, Public Prosecutor's Office's action with conventional methods of conflict resolution is also required.